(untitled) (Marketing Jurnali, 2025)
This thesis analyzes the issues of increasing the effectiveness of digital marketing strategies in the insurance market. The results show that artificial intelligence, big data analysis, social networks and mobile applications play an important role in meeting customer needs in the insurance sector.